PICTORIAL ELEMENTS OF INDIAN MINIATURE PAINTING - Rao, K. Mrutyunjaya (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper discusses the magnificent contribution of Indian miniature painting as the torch bearer of Indian visual culture for the future generations with transitions and various idioms. It’s Visual imagery raised to paramount importance from the auxiliary position to the religious text. Artist has not imitated from nature but imbibed the spirit of divinity and greater love and passion on Indian culture. Its function is religious as well as decorative. “Horrorvacuue” the desire of filling space is the common characteristics of an Indian is often appears in Indian painting. The articulations of line, colour , space are discussed in this article The Climatic conditions might been allowed the Indian painter to experience unusual color patterns. The deep rooted veneration for religion and nature and to fulfill the taste of his patron. Which made him as a distinct artist in the world forever.